Minimal Projections onto Subspaces with Codimension 2. (3rd August 2017) - Sokołowski, Filip
ABSTRACT: In this article, the relationship between absolute projection constants with dimension n and with codimension n is given. In particular, bounds from below are found for absolute projection constants with codimension 2. Also, exact formulas for minimal projections in this case are given. It is shown that these minimal projections are not unique.